FC036: A Clinical Workflow for Selection of Patients and Cost-Efficient Diagnosis of Genetic Kidney Diseases. (3rd May 2022) - Becherucci, Francesca; Cirillo, Luigi; Landini, Samuela; Palazzo, Viviana; Raglianti, Valentina; Lugli, Gianmarco; Tiberi, Lucia; Vaglio, Augusto; Anders, Hans-Joachim; Mazzinghi, Benedetta; Romagnani, Paola
Abstract: BACKGROUND AND AIMS: With the spread of whole-exome sequencing techniques (WES), genetic kidney diseases are increasingly recognized across all age groups. However, accessibility, interpretation of results and costs limit the widespread of genomics use in daily practice [1 ]. In the very last years, first experiences in the implementation of renal genetic services have been started [2 ]. In this work, we explored the feasibility and diagnostic performance of a service delivery model based on a territorial network for patients' selection, followed by referral to the renal genetic clinic of a tertiary centre for WES, results interpretation and counseling. We hypothesized that higher diagnostic yield and cost-effectiveness could be achieved by implementing a workflow that could solve three problems: (1) Give clear indications to the nephrologist about which patients with kidney diseases should undergo genetic testing, (2) Increase the rate and accuracy of genetic testing and evaluate the clinical impact and (3) Identify the kidney diseases for which early genetic testing is not only clinically, but also economically convenient for the healthcare provider based on pre-specified clinical criteria for tertiary centre referral. METHOD: We set up a multi-step diagnostic workflow. We established specific clinical criteria for evaluation of patients who should undergo genetic testing on the suspicion of a genetic disease by a network of nephrology centres. Patients selected were referred to a tertiary centre for genetic diagnosis by WES, reverse-phenotyping and multidisciplinary board analysis. This workflow has been applied to pediatric and adult patients with kidney diseases belonging to eight clinical categories (Podocytopathies, Collagenopathies, Tubulopathies, Unknown familial nephropathies, Ciliopathies, Congenital anomalies of the kidney and urinary tract, Syndromic chronic kidney disease and Metabolic kidney disorders). We recorded clinical-laboratory-radiological information of patients included. We also performed a cost-analysis of the diagnostic workflow modelling the possible economic saving using it. RESULTS: We included 402 patients, of note, 188 patients were female (46.8%) and 132 patients (33%) were >16 years of age. We obtained a global diagnostic yield of 69.2% (278–402), with category-specific diagnostic rates ranging from 38.5% to 87%. By reverse phenotyping, we reclassified diagnoses in 74–278 (26.6%) patients, thus increasing diagnostic accuracy. Overall, reverse phenotyping increased the diagnostic rate in an average of 20% of cases, irrespective of the age at clinical onset of the disease. Diagnostic yield was independent of the age at the onset of kidney disease. Genetic testing was offered as cascade screening to 67 families, providing a genetic diagnosis in 62 family members with previously unsuspected or unspecified kidney disorders. The clinical work-up changed and was redirected on average in 50% of patients. In 11.5% of patients, the results of genetic testing helped in guiding kidney transplant decisions. Finally, cost-analysis showed that our workflow is cost-efficient allowing to potentially save a mean of 1360 euros per patient. CONCLUSION: Ordering genetic testing, interpreting results, counselling patients and their families, and tailoring clinical management (i.e. personalized nephrology) is feasible and saves costs in a real-world setting.